1987
DOI: 10.1021/bi00382a002
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering of subtilisin BPN': enhanced stabilization through the introduction of two cysteines to form a disulfide bond

Abstract: Introduction of a disulfide bond by site-directed mutagenesis was found to enhance the stability of subtilisin BPN' (EC 3.4.21.14) under a variety of conditions. The location of the new disulfide bond was selected with the aid of a computer program, which scored various sites according to the amount of distortion that an introduced disulfide linkage would create in a 1.3-A X-ray model of native subtilisin BPN'. Of the several amino acid pairs identified by this program as suitable candidates, Thr-22 and Ser-87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(118 citation statements)
references
References 30 publications
0
118
0
Order By: Relevance
“…The weak stabilization of this crosslink may derive from a poor model of the N-state (the Escherichia coli enzyme crystal structure was used) or from a nonadherence to a two-state equilibrium. Novel disulfide bonds have been introduced into subtilisin BPN' (Wells & Powers, 1986;Pantoliano et al, 1987;Mitchinson & Wells, 1989), subtilisin E (Takagi et al, 1990), and troponin C (Gusev et al, 1991), but irreversible denaturation is observed for either the crosslinked or non-crosslinked forms or both, obviating thermodynamic treatment based on Equation 1.…”
Section: Novel Disulfidesmentioning
confidence: 99%
“…The weak stabilization of this crosslink may derive from a poor model of the N-state (the Escherichia coli enzyme crystal structure was used) or from a nonadherence to a two-state equilibrium. Novel disulfide bonds have been introduced into subtilisin BPN' (Wells & Powers, 1986;Pantoliano et al, 1987;Mitchinson & Wells, 1989), subtilisin E (Takagi et al, 1990), and troponin C (Gusev et al, 1991), but irreversible denaturation is observed for either the crosslinked or non-crosslinked forms or both, obviating thermodynamic treatment based on Equation 1.…”
Section: Novel Disulfidesmentioning
confidence: 99%
“…This structure was subsequently refined at 1.8 A resolution with phenyl methyl sulfonyl fluoride (PMSF) inhibitor covalently bound (Bott, Ultsch, Kossiakoff, Graycar, Katz & Power, 1988), in complex with Streptomyces inhibitor at 2.6 A (Hirono, Akagawa, Mitsui & Iitaka, 1984) and at 2.1 A as a complex with the chymotrypsin inhibitor 2 from barley seed (McPhalen, Svendsen, Jonassen & James, 1985;McPhalen & James, 1988). High-resolution structures of site-directed mutants of SBPN (Pantoliano et al, 1987(Pantoliano et al, , 1988 have also been reported. The three-dimensional structures of other Bacilli subtilisins have been published: the SBCARL-eglin-C complex at 1.8/k (McPhalen, Schnebli & Jamesl 1985;McPhalen & James, 1988) and independently at a nominal resolution of 1.2 A (Bode, Papamokos, Musil, Seemfiller & Fritz, 1986;Bode, Papamokos & Musil, 1987), and native SBCARL at 2.5A (Neidhart & Petsko, 1988).…”
Section: Bacteriummentioning
confidence: 99%
“…Genetically engineered mutants of subtilisin BPN' have been extensively investigated (e.g. Russell, Thomas & Fersht, 1987;Pantoliano, Ladner, Bryan, Rollence, Wood & Poulos, 1987;Pantoliano, Whitlow, Wood, Rollence, Finzel, Gilliland, Poulos & Bryan, 1988). In addition the subtilisins have extensive practical uses, mainly as additives to laundry detergents to improve their cleaning power by hydrolysis of protein stains.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge has, therefore, stimulated several attempts to introduce new disulfide bonds to improve protein stability. To date, disulfide bonds have been engineered into dihydrofolate reductase (2), T4 lysozyme (3,4), subtilisin (5,6), and A repressor (7). The addition of new disulfides has not, however, always increased stability.…”
mentioning
confidence: 99%
“…Nonreducing SDS/PAGE (5,6) and reversed-phase HPLC (3,4) have been used to assay the formation of disulfide bonds. However, neither SDS/PAGE nor reversed-phase HPLC was always effective in distinguishing between the oxidized (crosslinked) and reduced (noncrosslinked) form of the mutant lysozymes.…”
mentioning
confidence: 99%